Thermal and structural properties of tantalum alkali-phosphate glasses - Cordeiro, Luciano; Silva, Robson Manoel; Pietro, Gabriele Matinatti de; Pereira, Camila; Ferreira, Elivelton Alves; Ribeiro, Sidney José Lima [UNESP]; Messaddeq, Younes [UNESP]; Cassanjes, Fabia Castro; Poirier, Gael (Elsevier B.V., 2014)
In this work, tantalum alkali-phosphate glasses were prepared in the ternary system 0.9[(100 - x) NaPO3 - xTa(2)O(5)] - 0.1K(2)O with x varying from 0 to 20. The thermal properties as a function of Ta2O5 content were investigated by Differential Scanning Calorimetly and Differential Thermal Analysis in order to understand the influence of composition on glass transition temperatures and crystallization behaviors. Increasing Ta2O5 content leads to a drastic and linear increase of glass transition temperatures in agreement with the increasing viscosity of the melt observed during the synthesis. In addition, Ta2O5 incorporation results in high thermal stability against devitrification, suggesting the intermediary role of tantalum in the alkali-phosphate network. Comparison of powder and bulk thermal analyzes also pointed out a dominant surface crystallization mechanism for these glass samples. UV-visible absorption measurements proved the high visible transparency of the samples and a decrease of the optical bandgap energy with tantalum addition, suggesting an increase of the glass network covalency. Finally, vibrational spectroscopies performed by FTIR and Raman support the hypothesis of tantalum insertion inside the phosphate tetrahedral network with TaO6 units cross-linking the metaphosphate and pyrophosphate units. Thus, the intermediary behavior of tantalum increases the network connectivity with higher rigidity, glass transition temperatures and thermal stabilities against devitrification. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Glass; Structure; Phosphate; Tantalum